Influence of the TiO2 nanoparticles on upconversion luminescence of Er3+-doped and Er3+/Yb3+-codoped GeO2-PbO glasses - Gunji, R. M.; Mattos, G. R.S.; Bordon, C. D.S.; Garcia, J. A.M. [UNESP]; Gómez-Malagón, L. A.; Kassab, L. R.P. [UNESP] (Elsevier, 2022)
We report the effect of TiO2 nanoparticles (NPs) on the optical properties of Er3+-doped and Er3+/Yb3+-codoped GeO2-PbO glasses. The present investigation demonstrates the adequate experimental procedure to produce TiO2 NPs in anatase structure (size distribution of TiO2 NPs centered at ∼ 50 nm) that favors the infrared-to-visible frequency upconversion (UC) process in Er3+-doped and Er3+/Yb3+ codoped GeO2-PbO. The samples were produced with the melt-quenching technique; phase transformation from amorphous phase to anatase crystalline structure takes place during the annealing that was performed at 420 °C. The feasibility of obtaining GeO2-PbO glasses with improved UC, due to Er3+ ions located in low symmetry sites promoted by the anatase structure of TiO2 NPs and the UC mechanisms from Yb3+ to Er3+ ions is presented. Photoluminescence growth of about 40% (at ∼ 525 and 545 nm) was observed for the samples doped with Er3+ and TiO2 NPs in comparison with the one doped with Er3+ and without TiO2 NPs. Furthermore, an enhancement of ∼25% (525, 545 e 655 nm) was estimated for the UC intensity of samples codoped with Er3+/Yb3+ and with TiO2 NPs when compared with those without TiO2 NPs. The present investigation covers the lack of the literature related to the investigation of anatase structure of TiO2 NPs in Er3+-doped and Er3+/Yb3+ codoped GeO2-PbO glasses and can be extended to different hosts for different photonics applications.
Keywords: Anatase TiO2 nanoparticles; Germanate glasses; Glasses; Upconversion